Aqueous extract of Swietenia macrophylla leaf exerts an anti-inflammatory effect in a murine model of Parkinson’s disease induced by 6-OHDA - Cardoso, Váldina Solimar Lopes; Valente-Amaral, Anderson; Monteiro, Rayan Fidel Martins; Meira, Clarina Loius Silva; de Meira, Natália Silva; da Silva, Milton Nascimento; Pinheiro, João de Jesus Viana; Bastos, Gilmara de Nazareth Tavares; Felício, João Soares; Yamada, Elizabeth Sumi (Frontiers in Neuroscience, 2024)
Introduction Parkinson’s disease affects 2% of the population aged over 65 years and is the second most common neurodegenerative disorder in the general population. The appearance of motor symptoms is associated with the degeneration of dopaminergic neurons in the nigrostriatal pathway. Clinically significant nonmotor symptoms are also important for severe disability with disease progression. Pharmacological treatment with levodopa, which involves dopamine restitution, results in a temporary improvement in motor symptoms. Among the mechanisms underlying the pathogenesis of the disease are exacerbated oxidative stress, mitochondrial dysfunction, and neuroinflammation. A phytochemical prospecting study showed that the aqueous extract of the leaves from Swietenia macrophylla (Melineaceae), known as mahogany, has polyphenols with antioxidant and anti-inflammatory capacity in a significantly higher percentage than leaf extracts from other Amazonian plants. Furthermore, the antioxidant and anti-inflammatory capacity of aqueous extract of mahogany leaf has already been demonstrated in an in vitro model. In this study, we hypothesized that the aqueous extract of mahogany leaf (AEML) has a neuroprotective effect in a murine model of Parkinson’s disease induced by 6-hydroxidopamine (6-OHDA), due to antioxidant and anti-inflammatory properties of its phenolic compounds. Methods Mice were treated daily with the mahogany extract at a dose of 50 mg/kg, starting 7 days before 6-OHDA infusion until post-surgery day 7. Results and discussion The animals from the 6-OHDA/mahogany group, which corresponds to animals injected with the toxin and treated with aqueous extract of the mahogany leaf, presented distinct behavioral phenotypes after apomorphine challenge and were therefore subdivided into 2 groups, 6-OHDA/mahogany F1 and 6-OHDA/mahogany F2. The F1 group showed a significant increase in contralateral rotations, whereas the F2 group did not show rotations after the apomorphine stimulus. In the F1 group, there was an increase, although not significant, in motor performance in the open field and elevated plus maze tests, whereas in the F2 group, there was significant improvement, which may be related to the lesser degree of injury to the nigrostriatal dopaminergic pathway. The TH+ histopathological analysis, a dopaminergic neuron marker, confirmed that the lesion to the nigrostriatal dopaminergic pathway was more pronounced in 6-OHDA/mahogany F1 than in 6-OHDA/mahogany F2. Our main result consisted of signs of improvement in the inflammatory profile in both the F1 and F2 6-OHDA/mahogany groups, such as a lower number of IBA-1+ microglial cells in the ventral striatum and substantia nigra pars compacta and a reduction in GFAP+ expression, an astrocyte marker, in the dorsal striatum. In this study, several bioactive compounds in the aqueous extract of mahogany leaf may have contributed to the observed beneficial effects. Further studies are necessary to better characterize their applicability for treating chronic degenerative diseases with inflammatory and oxidative bases, such as Parkinson’s disease.